Musyawarah Nasional Kesatu ADAKSI sebagai Upaya Strategis Peningkatan Kesejahteraan dan Profesionalisme Dosen ASN - Eliyah A M Sampetoding; Harsi Admawati; Yulita Sirinti Pongtambing; Jonris Tampubolon; Esther Sanda Manapa (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
The First National Congress (MUNAS) of the Indonesian Civil Servant Lecturers Alliance under the Ministry of Education, Culture, Research, and Technology (ADAKSI), held on May 2–4, 2025, in Jakarta, served as a pivotal moment for the consolidation and advocacy of civil servant lecturers at the national level. This event successfully formulated the organization’s strategic direction, ratified its Statutes and Bylaws (AD/ART), and developed a medium-term work plan for 2025–2028. The inaugural MUNAS of ADAKSI also produced twenty strategic policy recommendations to the government, particularly concerning the welfare and professionalism of civil servant lecturers. In addition to electing the national executive board, the congress affirmed ADAKSI’s role as both a strategic partner and a critical counterpart to the government in higher education reform. This article not only outlines the key outcomes of the congress but also examines the contributions and impact of strengthening the institutional position of ministerial civil servant lecturers within the national education ecosystem.